Examining students linguistic and non-linguistic speaking issues and coping mechanisms in English presentations - Siti Khasinah; Saiful Akmal; Khairul Izza; Amiruddin Amiruddin; Muhammad Farhan (Universitas Syiah Kuala, 2024)
This study investigated types of speaking problems faced by students in English presentations and their strategies to overcome such problems. This was a mixed-method study, in which data were collected using a set of questionnaire and interviews. A purposive sampling technique was used to select students in the academic year of 2017 at the Department of English Language Education, Universitas Islam Negeri Ar-Raniry Banda Aceh. In addition, this study employed descriptive statistics to analyze the questionnaire data, and Miles data analysis approach to analyze interview data. The results reveal that the students encountered both linguistic and non-linguistic problems in their English presentations. Linguistic problems include incorrect grammar, lack of vocabulary, and inaccurate pronunciation. Meanwhile, non-linguistic problems include fear of making mistakes, nervousness, shyness, lack of confidence and motivation, and hesitation in using the mother tongue. To overcome these problems, students used several strategies, such as being physically and mentally well-prepared, memorizing the materials, and rehearsing the presentation materials. Furthermore, they also used other strategies, such as preparing notes and making minimal eye contact in their presentations. The result of this study is expected to offer a practical yet realistic reflection and anticipative coping strategies for English lecturers to address students problems in EFL speaking classrooms.